The Dynamics of Sharia Compliance in the Sharia Fintech Ecosystem in Indonesia: A Contemporary Fiqh Muamalah Analysis - Mhd. Iqbal; Rozi Andrini; Muhammad Adnan Azzaki (JAWI : Journal of Ahkam Wa Iqtishad, 2026)
The development of financial technology (fintech) has driven significant transformations in the financial system, including the emergence of  Islamic fintech as an alternative to digital financial services based on Islamic principles. However, rapid technological innovation also presents challenges related to sharia compliance, especially in ensuring the conformity of operational practices with the principles of fiqh muamalah. This study aims to analyze the dynamics of sharia compliance in the sharia fintech ecosystem in Indonesia through the perspective of contemporary fiqh muamalah The research method used is a qualitative approach with literature studies on relevant scientific journals, regulations, and fatwas. The results of the study show that normatively most sharia fintechs have adopted the principles of sharia compliance, but in practice there are still variations in implementation, especially related to the validity of digital contracts, information transparency, delay penalties, and the effectiveness of the supervision of the Sharia Supervisory Board. This research confirms that contemporary fiqh muamalah has a strategic role in bridging technological innovation with sharia principles, in order to realize a fair, sustainable, and maqāṣid al-sharia fintech ecosystem.